PNb9O25 nanofiber as a high-voltage anode material for advanced lithium ions batteries - Haoxiang Yu; Jundong Zhang; Maoting Xia; Chenchen Deng; Xikun Zhang; Runtian Zheng; Shi Chen; Jie Shu; Zhen-Bo Wang (Journal of Materiomics, 2020)
If the operating voltage of anode materials is below 1.0 V versus Li+/Li, the side reaction between electrolyte and anode materials will occur extensively. Thus, high-voltage anode materials have aroused interest recently. In this work, we report the preparation of PNb9O25 nanofiber via a facile electrospinning method. The PNb9O25 nanofiber shows the high rate performance and excellent cycling performance when it is used as anode in lithium ions batteries. For instance, the PNb9O25 nanofiber can deliver a capacity of 233, 212.1, 193.8, and 181.4 mA h g−1 at 0.2, 1, 3, and 6C, respectively. After 1000 cycles, it can reach at 134.3 mA h g−1 with capacity retention of 70.9%. Meanwhile, the ex situ X-ray photoelectron spectroscopy technique has been adopted to investigate the evolution in valence state of each element for PNb9O25 nanofiber. In addition, the PNb9O25 nanofiber is chosen as the anode material in lithium ion full cell in this work, demonstrating the potential for practical application.